Effect of Short-Term Treatment with Citrullus colocynthis L on the Lipid Profile and Other Blood Biochemical Parameters in Albino Rats - A. KHOURI, NABIL; EL-AKAWI, ZEYAD; DARADKA, HAYTHAM (Asian Journal of Chemistry, 2010)
The effect of Citrullus colocynthis L aqueous extract in 70% ethanol on blood biochemical parameters including: total cholesterol, triglycerides, total bilirubin, total protein, blood urea, serum creatine kinase (CK), serum lactate dehydrogenase (LDL), serum aspartate aminotransferase (AST) and serum alanine aminotransferase (ALT) were determined after oral administration of the extract to albino rats in a dose of 500mg/kg body weight for 7 d. A total of 20 rats were involved in this study and were divided into two groups. Group (A) a vehicle-treated control and group (B) a treated group with Citrullus colocynthis L. Our results demonstrated that administration of Citrullus colocynthis L in a dose of 500 mg/kg of body weight for 7 d induces a very significant decrease in total serum cholesterol level. The total cholesterol serum concentration was 180.1 ± 6.96 mg/dL in controls, while 135 ± 6.82 mg/dL in treated rats (p ≤ 0.01). In addition, a significant decrease in blood levels of both ALT and CK (p ≤ 0.05) and a significant increase in LDL blood serum level were found (p ≤ 0.01). Other parameters including, triglycerides, total bilirubin, total protein, blood urea and AST were also tested and their serum levels were found to be unchanged. In conclusion, the lowering effect of Citrullus colocynthis L on total cholesterol was very significant and this should be considered in the treatment of high cholesterol blood levels.